2009
DOI: 10.1592/phco.29.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Cardiovascular Disease

Abstract: The hormonal derivative of vitamin D, 1,25-dihydroxyvitamin D (1,25[OH](2)D) or calcitriol, has been implicated in many physiologic processes beyond calcium and phosphorus homeostasis, and likely plays a role in several chronic disease states, in particular, cardiovascular disease. Experimental data suggest that 1,25(OH)(2)D affects cardiac muscle directly, controls parathyroid hormone secretion, regulates the renin-angiotensin-aldosterone system, and modulates the immune system. Because of these biologic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 71 publications
1
75
1
3
Order By: Relevance
“…There are many beneficial components of low-fat dairy foods that may contribute to their protective effects, including minerals such as calcium, 32-34 magnesium 35 and potassium, 36 vitamin D in fortified dairy foods 37 and bioactive milk peptides. 38,39 Calcium is well understood to have a role in the protective effects of low-fat dairy foods; two independent meta-analyses of randomised controlled trials, 33,34 as well as a follow-up analysis 32 showed that calcium supplementation resulted in small, significant reductions in SBP, but had no effect on DBP.…”
Section: Discussionmentioning
confidence: 99%
“…There are many beneficial components of low-fat dairy foods that may contribute to their protective effects, including minerals such as calcium, 32-34 magnesium 35 and potassium, 36 vitamin D in fortified dairy foods 37 and bioactive milk peptides. 38,39 Calcium is well understood to have a role in the protective effects of low-fat dairy foods; two independent meta-analyses of randomised controlled trials, 33,34 as well as a follow-up analysis 32 showed that calcium supplementation resulted in small, significant reductions in SBP, but had no effect on DBP.…”
Section: Discussionmentioning
confidence: 99%
“…16 Animal studies have also shown a link between vitamin D deficiency and cardiovascular dysfunction including cardiac hypertrophy and hypertension. 16 Other studies of pregnant women have shown seasonal variations in rates of pregnancy-induced hypertension and pre-eclampsia, suggesting that vitamin D obtained from sunshine may possibly play a role in the development of pre-eclampsia or pregnancyinduced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…16 Animal studies have also shown a link between vitamin D deficiency and cardiovascular dysfunction including cardiac hypertrophy and hypertension. 16 Other studies of pregnant women have shown seasonal variations in rates of pregnancy-induced hypertension and pre-eclampsia, suggesting that vitamin D obtained from sunshine may possibly play a role in the development of pre-eclampsia or pregnancyinduced hypertension. 17,18 However, a recent study from New South Wales, Australia showed seasonal fluctuations in pre-eclampsia and pregnancy hypertension, and suggested that increased sunlight (a proxy for vitamin D) around the time of conception was associated with increased rates of pregnancy hypertension and pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Increased PTH for longer periods of time may indeed have harmful effects on the cardiovascular system (7,45,46,47,48,49). The possible effects of vitamin D on the cardiovascular system have been discussed thoroughly in several overviews (50,51,52,53).…”
Section: Discussionmentioning
confidence: 99%